Tracking tools of extracellular vesicles for biomedical research - Liu, Qisong; Huang, Jianghong; Xia, Jiang; Liang, Yujie; Li, Guangheng (Frontiers in Bioengineering and Biotechnology, 2022)
Imaging of extracellular vesicles (EVs) will facilitate a better understanding of their biological functions and their potential as therapeutics and drug delivery vehicles. In order to clarify EVs-mediate cellular communication in vitro and to track the bio-distribution of EVs in vivo, various strategies have been developed to label and image EVs. In this review, we summarized recent advances in tracking of EVs, demonstrating the methods for labeling and imaging of EVs, in which the labeling methods include direct and indirect labeling, and the imaging modalities include fluorescent imaging, bioluminescent imaging, radiolabeling assisted imaging, and nanoparticles assisted imaging. These techniques help us better understand the mechanism of uptake, the bio-distribution and the function of EVs. More importantly, we can evaluate the pharmacokinetic properties of EVs, which will help to promote their further clinical application.